Comparison of nine different methods to assess fish communities in lentic flood‐plain habitats. Issue 1 (22nd May 2017) - Mueller, M.; Pander, J.; Knott, J.; Geist, J.
Abstract : This study compares the effectiveness and representativeness of electrofishing, snorkelling, seining, baited lift netting, multi‐mesh gillnetting, baited fish traps, fyke netting, angling and longline fishing, considering three typical lentic flood‐plain habitats at different times of day. Electrofishing was by far the most effective method yielding highest species richness, species trait representation and catch per unit of effort (CPUE), followed by seining. For single species like dace Leuciscus leuciscus, European ruffe Gymnocephalus cernua, common bream Abramis brama and silver bream Blicca bjoerkna, seining was more effective than electrofishing. With both methods, some species were more consistently caught during night, dusk or dawn than during daylight. All other methods tested cannot be generally recommended for fish community assessments in shallow backwaters due to their low representativeness of species inventory and generally low CPUE. Based on these results, electrofishing of 30 m transect replicates at different times of day for monitoring the fish community in shallow backwaters, can be recommended, enabling the maximum possible comparability to adjacent river habitats. Seining should be considered as an alternative if accessibility of habitats is restricted or electrofishing is prohibited. The 25 species detected in the backwaters also suggest that these habitats contribute a large proportion of fish diversity and should be included in standard assessments of river ecological status.